2019
DOI: 10.1111/1750-3841.14753
|View full text |Cite
|
Sign up to set email alerts
|

Using Canola Oil Organogels as Fat Replacement in Liver Pâté

Abstract: Five canola oil organogel formulations were used to replace pork fat in pâtés to increase unsaturated fat content, and to determine their effects on texture and sensory properties. While pâtés made with canola oil were softer than the control pork fat product at room temperature, pâtés made with gelled canola oil (organogel pâtés) had similar hardness values to the control. Back extrusion results (also a measure of spreadability) showed that pâté made with canola oil only was softer than the control at 4 °C, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Sterol/sterol-ester [165][166][167][168] EC, wax [ 38,[168][169][170][171][172][173][174] Pork skin emulsion [175] Texture, spreadability Pâté EC, wax [ 176,177] EC+ MAG [178] Margarine+ spreads Emulsion stabilization, hardness, melting properties, spreadability…”
Section: Confectionary Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterol/sterol-ester [165][166][167][168] EC, wax [ 38,[168][169][170][171][172][173][174] Pork skin emulsion [175] Texture, spreadability Pâté EC, wax [ 176,177] EC+ MAG [178] Margarine+ spreads Emulsion stabilization, hardness, melting properties, spreadability…”
Section: Confectionary Productsmentioning
confidence: 99%
“…Oleogels with either 12 or 14 wt% EC and 1.5 or 3.0 wt% glycerol monostearate (GMS) in canola oil were used to reduce the SAFA content of a liver pâté formulation by 60%. [ 178 ] Additionally, two pâtés were produced with pure pork fat and canola oil, respectively. The authors showed that hardness of pâtés at room temperature could be mimicked using either 14% EC oleogel or a mixture of 12% EC + 3% GMS.…”
Section: Food Applicationsmentioning
confidence: 99%
“…Various studies describe EC-based oleogels as a potential possibility to reduce or eliminate the amount of saturated or trans-fats in foods by mimicking the physical characteristics of traditional fats whose structure is based on TAG crystal networks (Co & Marangoni, 2012;Wang, Gravelle, Blake, & Marangoni, 2016). Various studies have investigated the application of such oleogels in different foods, including different emulsion-type sausages such as frankfurters, breakfast sausages, and liver pâté (Barbut, Marangoni, Thode, & Tiensa, 2019;Barbut, Wood, & Marangoni, 2016;Davidovich-Pinhas, Barbut, & Marangoni, 2018;Zetzl, Marangoni, & Barbut, 2012).…”
Section: Food Engineering Materials Science and Nanotechnologymentioning
confidence: 99%
“…Some studies have been carried out to improve the fatty acid profile of cooked (frankfurter sausages) or fresh meat products (patties, longanizas, merguez) by using solid lipid material based on emulsion gels or oleogels [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, there are very few studies of this kind on fermented meat products.…”
Section: Introductionmentioning
confidence: 99%